A CORRELATION BETWEEN THE USE OF INTERNET AS LEARNING SOURCE, LEARNERS’ LEARNING AUTONUMOUS AND LEARNERS’ ENGAGEMENT IN LEARNING PROCESS - Riwanda, Agus; Fani, Armin; Islamy, M. Irfan (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
In recent teaching learning process, learners are treated as active processor of knowledge which requires learners’ engagement in teaching learning process. As an active process, learners’ engagement is influenced by several factors. This study investigates the correlation between the use of internet as learning sources, learners’ learning autonomous and learners’ engagement in teaching learning process. Further, this study also investigates factors that might influence learners’ engagement in teaching learning process. Mixed method with sequential explanatory design was administered as approach in this research. Data of this research were taken through questionnaire, interview, and observation. Quantitative and qualitative analysis were administered to analyze the data in order to answer the research questions. The result of this study reveals that there is significant correlation between internet use, learners’ learning autonomous and learners’ engagement. The study also reveals several factors that influence learners’ engagement in teaching learning process. Investigating the effect of learners’ attributes and learning milieu are recommended for future research.